BENTUK PENILAIAN DALAM PELAKSANAAN LAYANAN KONSELING PERORANGAN OLEH GURU BK DI SMA PGRI 1 PADANG - Asmaneli, Asmaneli; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2014)
The background of the research is the valuation in each successive of individual counseling by guidance and counseling teacher at Senior High School PGRI 1 Padang which is still done improperly as it is hoped. The research focus is (1) the form of process appraisal in each successive of individual counseling, (2) the form of outcome appraisal in each successive of individual counseling. The research design is descriptive qualitative, by using snowball sampling to get the sample. The research informants are two guidance and counseling teachers of Senior High School PGRI 1, and the supportive informants are seven students of Senior High School PGRI 1 who involve in each successive of individual counseling. The data is accumulated by interview. Then, the data is analyzed in three steps: (1) data reduction, (2) data presentation , (3) conclusion. The test result indicates that the appraisals done by the guidance and counseling teacher are: 1) process appraisal 2) outcome appraisal. The outcome appraisal is done in three steps likely, immediate, short term, and long term. This appraisals are Understanding, Comfort, Action (UCA).Â